Lives and Afterlives: The Hiberno-Latin Patrician Tradition, 650-1100. By Elizabeth Dawson. Studia Traditionis Theologiae, vol. 55. Turnhout. Belgium: Brepols Publishers, 2023. 179 pp. € 70,00 (Paperback), €70,00 (E-book) - Higgins, John (Church history, 2024)
Lives and Afterlives: The Hiberno-Latin Patrician Tradition, 650-1100. By Elizabeth Dawson. Studia Traditionis Theologiae, vol. 55. Turnhout. Belgium: Brepols Publishers, 2023. 179 pp. € 70,00 (Paperback), €70,00 (E-book). - Volume 93 Issue 3.